Battery cell, secondary battery, and electric device

By optimizing the particle size and doping elements of the positive electrode active material in lithium iron phosphate batteries, combined with the use of conductive agents, the problem that lithium iron phosphate batteries cannot take into account high power density and high cycling performance, and the high efficiency and long battery life are achieved life.

CN119275242APending Publication Date: 2025-01-07CONTEMPORARY AMPEREX TECHNOLOGY CO LTD

Patent Information

Application Number
CN202411824624.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-12
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

Existing lithium iron phosphate batteries cannot take into account both high power density and high cycling performance, and there are problems such as too small particle size leading to structural instability and increasing side reactions.

Method used

By controlling the volume particle size distribution of the positive electrode active material and the type and amount of doped elements, combined with the use of carbon nanotubes and carbon black, the structure and material composition of the electrode sheet are optimized, and the lattice stability and conductive properties of the material are improved.

Benefits of technology

It significantly improves the power and cycling performance of the battery, extends the service life of the battery, and improves the energy density.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119275242A_ABST
    Figure CN119275242A_ABST
Patent Text Reader

Abstract

The invention provides a battery monomer, a secondary battery and an electric device, and belongs to the field of batteries. The battery monomer comprises a positive electrode plate, the positive electrode plate comprises a positive electrode active material layer, the positive electrode active material layer comprises a positive electrode active material, and the volume particle size distribution Dv50 of the positive electrode active material is 0.3 [mu] m-3 [mu] m; the volume particle size distribution Dv10 is 100-800 nm, the volume particle size distribution Dv99 is less than 20 [mu] m, the positive electrode active material comprises M-doped lithium iron phosphate, M comprises Al and / or at least one transition metal element except Fe, and the mass content of M in the M-doped lithium iron phosphate is 200-1500 ppm. According to the present invention, the particle size of the positive electrode active material, the type of the doping element and the doping amount are simultaneously regulated and controlled in the above range, and the parameters are matched and co-act so as to provide the good cycle performance on the basis of the high power performance of the battery monomer.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of lithium batteries, and in particular to a battery cell, a secondary battery and an electrical device. Background Art

[0002] In recent years, as the application scope of lithium-ion batteries has become increasingly wider, lithium-ion batteries have been widely used in energy storage power systems such as hydropower, thermal power, wind power and solar power stations, as well as power tools, electric bicycles, electric motorcycles, electric vehicles, military equipment, aerospace and other fields.

[0003] Lithium iron phosphate is a positive electrode material with an olivine crystal structure and is one of the most commercially used positive electrode materials for lithium-ion batteries. Existing lithium iron phosphate batteries cannot achieve both high power density and high cycle performance and need to be further optimized. Summary of the invention

[0004] The present application is made in view of the above-mentioned problems, and its purpose is to provide a battery cell, a secondary battery and an electrical device so that the lithium iron phosphate battery has high power performance while taking into account better cycle performance.

[0005] In order to achieve the above objectives, the present application provides a battery cell, a secondary battery and an electrical device.

[0006] A first aspect of the present application provides a battery cell, comprising a positive electrode plate, the positive electrode plate comprising a positive electrode active material layer, the positive electrode active material layer comprising a positive electrode active material, the volume particle size distribution Dv50 of the positive electrode active material being 0.3 μm-3 μm, the volume particle size distribution Dv10 being 100 nm-800 nm, and the volume particle size distribution Dv99 being less than 20 μm; The positive electrode active material includes M-doped lithium iron phosphate, M includes Al and / or at least one transition metal element except Fe, and the mass proportion of M in the M-doped lithium iron phosphate is 200ppm-1500ppm.

[0007] Therefore, the battery cell provided by the present application controls the volume particle size distribution Dv50 of the positive electrode active material within the above range, limits the particle size of the positive electrode active material to be small, and makes its specific surface area large, which is beneficial to reduce the interface transfer impedance and significantly improve the power performance of the secondary battery. By limiting Dv10 and Dv99 within the above range to limit the particle size distribution, the particle size of the positive electrode active material is small and the particle size distribution is concentrated, which is beneficial to further improve the cycle performance and power of the battery cell. At the same time, by doping the lithium iron phosphate, by controlling the type of doping elements to include Al and / or at least one transition metal element other than Fe, and controlling the mass proportion of M in the M-doped lithium iron phosphate to be 200ppm-1500ppm, the lithium iron phosphate material is structurally modified to improve its lattice stability, effectively improve the cycle performance, and at the same time, it also has a certain improvement effect on its power performance.

[0008] That is, the battery cell provided in the present application simultaneously regulates the particle size of the positive electrode active material, the type of doping element and the doping amount within the above range, and the various parameters cooperate with each other to ensure that the battery cell has high power performance while also taking into account better cycle performance.

[0009] In any embodiment, the mass proportion of M in the M-doped lithium iron phosphate is 300ppm-1500ppm. Controlling the mass proportion of M in the M-doped lithium iron phosphate within the above range is conducive to optimizing the power performance and cycle performance of the battery cell.

[0010] In any embodiment, the transition metal element includes at least one of Mn, V, Ti, Zr, Ni, Co, and Nb. By doping the lithium iron phosphate with the above doping elements, it is beneficial to improve the stability of the material structure and improve the power performance and cycle performance of the battery cell.

[0011] In any embodiment, the specific surface area of ​​the positive electrode active material is 10 m 2 / g-20m 2 / g. The positive electrode active material has a large specific surface area, which is beneficial to reducing the interface transfer impedance and significantly improving the power performance of the battery cell.

[0012] In any embodiment, the mass proportion of M inside the M-doped lithium iron phosphate is less than the mass proportion of M on the surface of the M-doped lithium iron phosphate. Enriching the M element on the surface of the M-doped lithium iron phosphate particles is beneficial to improving the interface stability and the cycle stability of the battery cell.

[0013] In any embodiment, the positive electrode active material layer further includes a shell layer coated on the surface of the M-doped lithium iron phosphate. wherein the shell comprises carbon; and / or; The shell layer accounts for 1%-5% of the mass of the positive electrode active material; and / or; The thickness of the shell layer is 1 nm to 10 nm. Controlling the mass of the shell layer in the positive electrode active material and / or the thickness of the shell layer in the above range is beneficial to improving the energy density and cycle performance of the battery.

[0014] In any embodiment, the positive electrode active material layer includes a conductive agent, and the conductive agent includes carbon nanotubes. The selection of carbon nanotubes can effectively improve the conductivity of the pole piece and reduce the expansion of the pole piece during the cycle, thereby improving the power performance and cycle performance of the secondary battery.

[0015] In any embodiment, the carbon nanotube is a single-walled carbon nanotube, and the specific surface area of ​​the carbon nanotube is 400 m 2 / g-1600m 2 / g, tube diameter is 1.2nm-4.8nm, and tube length is greater than 50nm. Selecting single-walled carbon nanotubes in the above range can improve the conductivity of the pole piece and reduce the expansion of the pole piece during the cycle, thereby improving the power performance and cycle performance.

[0016] In any embodiment, the conductive agent further comprises carbon black. The combination of carbon black and carbon nanotubes can achieve better conductivity, and carbon black can improve electrolyte wetting and ion conductivity, which is beneficial to improving battery power performance and cycle performance.

[0017] In any embodiment, the positive electrode active material layer includes a binder; Wherein, the weight average molecular weight of the binder satisfies 40W-150W; and / or, The binder includes at least one of polyvinylidene fluoride, polytetrafluoroethylene, polyacrylic acid, polyvinyl alcohol, polyacrylonitrile and polyolefin.

[0018] In any embodiment, the positive electrode active material layer includes, by mass percentage, 95%-99% of the positive electrode active material, 0.2%-1% of the conductive agent, 0.5%-3% of the binder, and 0-1% of the surfactant.

[0019] In any embodiment, the positive electrode sheet further includes a positive electrode current collector and a primer layer, wherein the primer layer is disposed between the positive electrode current collector and the positive electrode active material layer.

[0020] A second aspect of the present application further provides a secondary battery, the secondary battery comprising the battery cell provided in the first aspect.

[0021] The second aspect of the present application further provides an electrical device, the electrical device comprising the secondary battery provided in the second aspect. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Various other advantages and benefits will become apparent to those of ordinary skill in the art by reading the detailed description of the preferred embodiments below. The accompanying drawings are only for the purpose of illustrating the preferred embodiments and are not to be considered as limiting the present application. Moreover, the same reference numerals are used throughout the drawings to represent the same components. In the drawings: Figure 1 A schematic diagram of the structure of a vehicle provided in some embodiments of the present application; Figure 2 A schematic diagram of the exploded structure of a secondary battery provided in some embodiments of the present application; Figure 3 A schematic diagram of the structure of a battery cell provided in some embodiments of the present application; Figure 4 An exploded view of a battery cell provided for some embodiments of the present application.

[0023] The reference numerals in the specific implementation manner are as follows: 1000-vehicle; 100-secondary battery; 200-motor; 300-controller; 10-housing; 11-accommodating space; 12-first part; 13-second part; 20-battery cell; 21-housing; 211-opening; 22-end cover assembly; 221-end cover; 222-electrode terminal; 23-electrode assembly; 24-current collecting member; 25-insulating protection member. DETAILED DESCRIPTION

[0024] Below, the embodiments of the positive electrode plate, secondary battery and electric device of the present application are specifically disclosed in detail with appropriate reference to the drawings. However, there may be cases where unnecessary detailed descriptions are omitted. For example, there are cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structure are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art. In addition, the drawings and the following descriptions are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.

[0025] "Scope" disclosed in the present application is limited in the form of lower limit and upper limit, and a given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of a special range. The scope limited in this way can be including end values ​​or not including end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a scope. For example, if the scope of 60-120 and 80-110 is listed for a specific parameter, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range values ​​1 and 2 are listed, and if the maximum range values ​​3, 4 and 5 are listed, the following scope can be all expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In the present application, unless otherwise specified, the numerical range "ab" represents the abbreviation of any real number combination between a and b, wherein a and b are real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.

[0026] If not otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.

[0027] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.

[0028] Unless otherwise specified, all steps of the present application may be performed sequentially or randomly, preferably sequentially. For example, a method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, a method may also include step (c), which means that step (c) may be added to the method in any order, for example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.

[0029] If there is no special explanation, the "include" and "comprising" mentioned in this application represent open-ended or closed-ended expressions. For example, "include" and "comprising" may represent that other components not listed may also be included or only listed components may be included or only listed components may be included.

[0030] If not specifically stated, in this application, the term "or" is inclusive. For example, the phrase "A or B" means "A, B, or both A and B". More specifically, any of the following conditions satisfies the condition "A or B": A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).

[0031] Compared with other positive electrode materials, lithium iron phosphate materials have the advantages of better structural stability and cycle stability. However, the lithium ion diffusion coefficient of lithium iron phosphate materials themselves is low, and the electronic conductivity is poor, resulting in poor power performance. In order to improve its power performance, it is usually chosen to reduce its particle size as much as possible to shorten the solid phase transmission distance to improve the kinetics. However, reducing the particle size means an increase in active reaction sites, which will lead to an increase in side reactions of lithium iron phosphate materials, an increase in Fe dissolution during the cycle, and an unstable structure, which affects the cycle life. In other words, the existing secondary batteries with lithium iron phosphate as the positive electrode material have the problem of not being able to take into account both high power density and high cycle performance.

[0032] Based on the above considerations, in order to realize a secondary battery with lithium iron phosphate as a positive electrode material while taking into account high power density and high cycle performance, the present application proposes a battery cell, which includes a positive electrode plate, the positive electrode plate includes a positive electrode active material layer, the positive electrode active material layer includes a positive electrode active material, the volume particle size distribution Dv50 of the positive electrode active material is 0.3μm-3μm, the volume particle size distribution Dv10 is 100nm-800nm, and the volume particle size distribution Dv99 is less than 20μm; The positive electrode active material includes M-doped lithium iron phosphate, M includes Al and / or at least one transition metal element except Fe, and the mass proportion of M in the M-doped lithium iron phosphate is 200ppm-1500ppm.

[0033] The battery cell provided in the present application controls the volume particle size distribution Dv50 of the positive electrode active material within the above range, limits the particle size of the positive electrode active material to be small, and makes its specific surface area large, which is beneficial to reduce the interface transfer impedance and significantly improve the power performance of the secondary battery. By limiting Dv10 and Dv99 within the above range to limit the particle size distribution, the particle size of the positive electrode active material is small and the particle size distribution is concentrated, which is beneficial to further improve the cycle performance and power of the battery cell. At the same time, by doping the lithium iron phosphate, by controlling the type of doping elements to include Al and / or at least one transition metal element other than Fe, and controlling the mass proportion of M in the M-doped lithium iron phosphate to be 200ppm-1500ppm, the lithium iron phosphate material is structurally modified to improve its lattice stability, effectively improve the cycle performance, and at the same time, it also has a certain improvement effect on its power performance.

[0034] That is, the battery cell provided in the present application, by simultaneously regulating the particle size of the positive electrode active material, the type of doping element and the doping mass ratio within the above-mentioned range, and by the coordinated action of various parameters, the battery cell can have both high power performance and better cycle performance.

[0035] The secondary battery can be used in, but is not limited to, electrical equipment such as vehicles, ships or aircraft, and a power supply system of the electrical equipment can be formed using the secondary battery disclosed in the present application.

[0036] The embodiment of the present application provides an electric device using a battery as a power source, and the electric device may be, but is not limited to, a mobile phone, a tablet, a laptop, an electric toy, an electric tool, a battery car, an electric car, a ship, a spacecraft, etc. Among them, the electric toy may include a fixed or mobile electric toy, for example, a game console, an electric car toy, an electric ship toy, an electric airplane toy, etc., and the spacecraft may include an airplane, a rocket, a space shuttle, a spacecraft, etc.

[0037] For the convenience of description, the following embodiments are described by taking a vehicle as an example of an electrical device in an embodiment of the present application.

[0038] Please refer to Figure 1 , Figure 1 A schematic diagram of the structure of a vehicle provided for some embodiments of the present application. The vehicle 1000 may be a fuel vehicle, a gas vehicle or a new energy vehicle, and the new energy vehicle may be a pure electric vehicle, a hybrid vehicle or an extended-range vehicle, etc. A secondary battery 100 is provided inside the vehicle 1000, and the secondary battery 100 may be provided at the bottom, head or tail of the vehicle 1000. The secondary battery 100 may be used to power the vehicle 1000, for example, the secondary battery 100 may be used as an operating power source for the vehicle 1000. The vehicle 1000 may also include a controller 300 and a motor 200, and the controller 300 is used to control the secondary battery 100 to power the motor 200, for example, for starting, navigating and driving the vehicle 1000. Working power requirements.

[0039] In some embodiments of the present application, the secondary battery 100 can be used not only as an operating power source for the vehicle 1000 , but also as a driving power source for the vehicle 1000 , replacing or partially replacing fuel or natural gas to provide driving power for the vehicle 1000 .

[0040] In the present application, the secondary battery 100 may refer to a single battery cell 20, or it may refer to a single physical module including multiple battery cells 20 to provide higher voltage and capacity, which may be in the form of a battery pack, a battery module, etc. The secondary battery 100 may include a case 10 for encapsulating multiple battery cells 20, and the case 10 may prevent liquid or other foreign matter from affecting the charging or discharging of the battery cells 20.

[0041] Figure 2 This is a schematic diagram of the exploded structure of a secondary battery 100 provided in some embodiments of the present application. Figure 2 The secondary battery 100 includes a housing 10 and a battery cell 20 , and the battery cell 20 is accommodated in the housing 10 .

[0042] The box body 10 is used to provide a storage space 11 for the battery cell 20. In some embodiments, the box body 10 may include a first portion 12 and a second portion 13, and the first portion 12 and the second portion 13 cover each other to define the storage space 11 for accommodating the battery cell 20. Of course, the connection between the first portion 12 and the second portion 13 can be sealed by a sealing member (not shown in the figure), and the sealing member can be a sealing ring, a sealant, etc.

[0043] The first part 12 and the second part 13 can be in various shapes, such as a cuboid, a cylinder, etc. The first part 12 can be a hollow structure with one side open to form a receiving cavity for receiving the battery cell 20, and the second part 13 can also be a hollow structure with one side open to form a receiving cavity for receiving the battery cell 20. The opening side of the second part 13 covers the opening side of the first part 12, thereby forming a box body 10 with a receiving space 11. Of course, if Figure 2 As shown, the first part 12 may be a hollow structure with one side open, and the second part 13 may be a plate-like structure. The second part 13 covers the open side of the first part 12 to form a box body 10 with an accommodating space 11.

[0044] In the secondary battery 100, there can be one or more battery cells 20. If there are more than one battery cell 20, the battery cells 20 can be connected in series, in parallel or in a mixed connection. A mixed connection means that the battery cells 20 are connected in series and in parallel. The battery cells 20 can be directly connected in series, in parallel or in a mixed connection, and then the whole formed by the battery cells 20 is accommodated in the box 10; of course, the battery cells 20 can be connected in series, in parallel or in a mixed connection to form a battery module, and then the battery modules are connected in series, in parallel or in a mixed connection to form a whole, and then accommodated in the box 10. The battery cell 20 can be cylindrical, flat, rectangular or in other shapes. Figure 2 The example shows that the battery cell 20 is in a square shape.

[0045] In some embodiments, the secondary battery 100 may further include a busbar component (not shown), and the multiple battery cells 20 may be electrically connected via the busbar component to achieve series connection, parallel connection, or mixed connection of the multiple battery cells 20 .

[0046] Figure 3 This is a schematic diagram of the structure of a battery cell 20 provided in some embodiments of the present application. Figure 4 This is an exploded view of a battery cell 20 provided in some embodiments of the present application. Figure 3 and Figure 4 The battery cell 20 may include a housing 21 , an end cap assembly 22 and an electrode assembly 23 . The housing 21 has an opening 211 , the electrode assembly 23 is accommodated in the housing 21 , and the end cap assembly 22 is used to cover the opening 211 .

[0047] The shape of the housing 21 can be determined according to the specific shape of the electrode assembly 23. For example, if the electrode assembly 23 is a rectangular parallelepiped structure, the housing 21 can be a rectangular parallelepiped structure. Figure 3 and Figure 4 The case where the housing 21 and the electrode assembly 23 are square is exemplarily shown.

[0048] The shell 21 may also be made of a variety of materials, such as copper, iron, aluminum, stainless steel, aluminum alloy, etc., and the embodiment of the present application does not impose any special restrictions on this.

[0049] The end cap assembly 22 includes an end cap 221 and an electrode terminal 222. The end cap assembly 22 is used to seal the opening 211 of the housing 21 to form a closed installation space (not shown), and the installation space is used to accommodate the electrode assembly 23. The installation space is also used to accommodate an electrolyte, such as an electrolyte. The end cap assembly 22 is a component for outputting the electrical energy of the electrode assembly 23. The electrode terminal 222 in the end cap assembly 22 is used to be electrically connected to the electrode assembly 23, that is, the electrode terminal 222 is electrically connected to the tab of the electrode assembly 23. For example, the electrode terminal 222 is connected to the tab through the current collecting member 24 to achieve electrical connection between the electrode terminal 222 and the tab.

[0050] It should be noted that the opening 211 of the shell 21 can be one or two. If the opening 211 of the shell 21 is one, the end cap assembly 22 can also be one, and two electrode terminals 222 can be provided in the end cap assembly 22, and the two electrode terminals 222 are respectively used to electrically connect to the positive pole ear and the negative pole ear of the electrode assembly 23. If the opening 211 of the shell 21 is two, for example, the two openings 211 are provided on opposite sides of the shell 21, and the end cap assembly 22 can also be two, and the two end cap assemblies 22 are respectively covered at the two openings 211 of the shell 21. In this case, the electrode terminal 222 in one end cap assembly 22 can be a positive electrode terminal, which is used to electrically connect to the positive pole ear of the electrode assembly 23; the electrode terminal 222 in the other end cap assembly 22 can be a negative electrode terminal, which is used to electrically connect to the negative pole piece of the electrode assembly 23.

[0051] In some embodiments, Figure 4As shown, the battery cell 20 may further include an insulating protective member 25 fixed to the periphery of the electrode assembly 23, and the insulating protective member 25 is used to insulate and isolate the electrode assembly 23 from the housing 21. Exemplarily, the insulating protective member 25 is a tape bonded to the periphery of the electrode assembly 23. In some embodiments, there are multiple electrode assemblies 23, and the insulating protective member 25 is arranged around the periphery of the multiple electrode assemblies 23, and the multiple electrode assemblies 23 are formed into an integral structure to keep the electrode assembly 23 structurally stable.

[0052] The electrode assembly 23 includes a positive electrode sheet, a negative electrode sheet and a separator. The electrode assembly 23 can be a wound electrode assembly 23 or a laminated electrode assembly 23, but the present application is not limited thereto.

[0053] The positive electrode sheet includes a positive electrode collector and a positive electrode active material layer. The positive electrode active material layer is coated on the surface of the positive electrode collector. The positive electrode collector not coated with the positive electrode active material layer protrudes from the positive electrode collector coated with the positive electrode active material layer. The positive electrode collector not coated with the positive electrode active material layer serves as a positive electrode tab.

[0054] In some embodiments, the positive electrode current collector may be a metal foil or a composite current collector. For example, aluminum foil may be used as the metal foil. The composite current collector may include a polymer material base and a metal layer formed on at least one surface of the polymer material base. The composite current collector may be formed by forming a metal material (aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).

[0055] The positive electrode active material layer includes a positive electrode active material.

[0056] In some embodiments, the positive electrode active material layer may further optionally include a binder. As an example, the binder may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorine-containing acrylate resin.

[0057] In some embodiments, the positive electrode active material layer may further include a conductive agent. As an example, the conductive agent may include at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.

[0058] In some embodiments, the positive electrode sheet can be prepared in the following manner: the components for preparing the positive electrode sheet, such as the positive electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent (such as N-methylpyrrolidone) to form a positive electrode slurry; the positive electrode slurry is coated on the positive electrode collector, and after drying, cold pressing and other processes, the positive electrode sheet can be obtained.

[0059] The negative electrode sheet includes a negative electrode collector and a negative electrode active material layer. The negative electrode active material layer is coated on the surface of the negative electrode collector. The negative electrode collector not coated with the negative electrode active material layer protrudes from the negative electrode collector coated with the negative electrode active material layer. The negative electrode collector not coated with the negative electrode active material layer serves as a negative electrode tab.

[0060] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. For example, as the metal foil, a copper foil may be used. The composite current collector may include a polymer material base layer and a metal layer formed on at least one surface of the polymer material substrate. The composite current collector may be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).

[0061] In some embodiments, the negative electrode active material layer includes a negative electrode active material, and the negative electrode active material may be a negative electrode active material for a battery known in the art. As an example, the negative electrode active material may include at least one of the following materials: artificial graphite, natural graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials, lithium titanate, etc. The silicon-based material may be selected from at least one of elemental silicon, silicon oxide compounds, silicon-carbon composites, silicon-nitrogen composites, and silicon alloys. The tin-based material may be selected from at least one of elemental tin, tin oxide compounds, and tin alloys. However, the present application is not limited to these materials, and other traditional materials that can be used as negative electrode active materials for batteries may also be used. These negative electrode active materials may be used alone or in combination of two or more.

[0062] In some embodiments, the negative electrode active material layer may further include a binder. The binder may be selected from at least one of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA) and carboxymethyl chitosan (CMCS).

[0063] In some embodiments, the negative electrode active material layer may further include a conductive agent, which may be selected from at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.

[0064] In some embodiments, the negative electrode active material layer may further optionally include other additives, such as a thickener (eg, sodium carboxymethyl cellulose (CMC-Na)).

[0065] In some embodiments, the negative electrode sheet can be prepared in the following manner: the components for preparing the negative electrode sheet, such as the negative electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent (such as deionized water) to form a negative electrode slurry; the negative electrode slurry is coated on the negative electrode collector, and after drying, cold pressing and other processes, the negative electrode sheet can be obtained.

[0066] In other embodiments, the current collector of the negative electrode plate may also generally include a current collector body and an undercoat layer. The undercoat layer may be disposed on at least one side of the current collector body. The undercoat layer substantially does not contain negative electrode active materials and may include a small amount of carbon material. However, the thickness of the coating formed by the carbon material is thin and cannot function as a negative electrode active material. In this embodiment, the negative electrode plate may be a plate without a negative electrode active material layer. For a negative electrode plate without a negative electrode active material layer, when the current collector of the negative electrode plate does not contain an undercoat layer, the film layer of the negative electrode plate may be disposed on the surface of at least one side of the current collector body; when the current collector of the negative electrode plate includes an undercoat layer, the film layer of the negative electrode plate may be disposed on the surface of the undercoat layer on the side away from the current collector body.

[0067] In some embodiments, in order to ensure that a large current can be passed without melting, the number of positive electrode tabs is multiple and they are stacked together, and the number of negative electrode tabs is multiple and they are stacked together.

[0068] The present application has no particular limitation on the type of isolation membrane, and any known porous isolation membrane with good chemical stability and mechanical stability can be selected.

[0069] In some embodiments, the material of the isolation membrane can be selected from at least one of glass fiber, non-woven fabric, polyethylene, polypropylene and polyvinylidene fluoride. The isolation membrane can be a single-layer film or a multi-layer composite film, without particular limitation. When the isolation membrane is a multi-layer composite film, the materials of each layer can be the same or different, without particular limitation.

[0070] The electrolyte plays the role of conducting ions between the positive electrode and the negative electrode. The present application has no specific restrictions on the type of electrolyte, which can be selected according to needs. For example, the electrolyte can be liquid, gel or all-solid.

[0071] In some embodiments, the electrolyte is an electrolyte solution, which includes an electrolyte salt and a solvent.

[0072] In some embodiments, the electrolyte salt can be selected from at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium hexafluoroarsenate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium trifluoromethanesulfonate, lithium difluorophosphate, lithium difluorooxalatoborate, lithium dioxalatoborate, lithium difluorodioxalatophosphate, and lithium tetrafluorooxalatophosphate.

[0073] In some embodiments, the solvent can be selected from at least one of ethylene carbonate, propylene carbonate, ethyl methyl carbonate, diethyl carbonate, dimethyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, butylene carbonate, fluoroethylene carbonate, methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, cyclopentane sulfone, dimethyl sulfone, methyl ethyl sulfone and diethyl sulfone.

[0074] In some embodiments, the electrolyte may further include additives, such as negative electrode film-forming additives, positive electrode film-forming additives, and additives that can improve certain battery properties, such as additives that improve battery overcharge performance, additives that improve battery high or low temperature performance, etc.

[0075] The embodiment of the present application provides a battery cell, which includes a positive electrode plate, the positive electrode plate includes a positive electrode active material layer, the positive electrode active material layer includes a positive electrode active material, the volume particle size distribution Dv50 of the positive electrode active material is 0.3 μm-3 μm, the volume particle size distribution Dv10 is 100 nm-800 nm, and the volume particle size distribution Dv99 is less than 20 μm; The positive electrode active material comprises M-doped lithium iron phosphate, wherein M comprises Al and / or at least one transition metal element except Fe, and the doping mass of M in the M-doped lithium iron phosphate is 200ppm-1500ppm.

[0076] For the volume particle size distribution Dv50, Dv10 and Dv99 of the positive electrode active material in the positive electrode sheet, the positive electrode active material scraped from the electrode sheet can be tested by laser diffraction method. Among them, the laser diffraction method includes the use of: equipment model: Malvern 2000 (MasterSizer2000) laser particle size analyzer, reference standard process: GB / T19077-2016 / ISO13320:2009, specific test process: take an appropriate amount of the sample to be tested (the sample concentration can ensure 8-12% shading), add 20ml of deionized water, and at the same time, ultraviolet for 5min (53KHz / 120W) to ensure that the sample is completely dispersed, and then measure the sample according to GB / T19077-2016 / ISO13320:2009 standard to obtain the volume particle size distribution Dv10, Dv50 and Dv99 of the positive electrode active material.

[0077] The test method for the mass proportion of M in M-doped lithium iron phosphate is as follows: the positive electrode active material is placed in an appropriate amount of concentrated nitric acid solvent for digestion, and digested by plate digestion method, and finally 7% (volume fraction of acid) hydrochloric acid is used to dissolve the solvent, and then the obtained solution is fixed to an appropriate volume and tested using an inductively coupled plasma emission spectrometer ICP=OES. The total mass of the lithium iron phosphate body and the mass of M are calculated by molecular formula according to the mass of P and Fe elements, and the mass proportion of M in M-doped lithium iron phosphate can be obtained. Among them, if the positive electrode active material contains a carbon coating layer, since the carbon coating layer will not be digested, it will not affect the test results.

[0078] By controlling the volume particle size distribution Dv50 of the positive electrode active material within the above range, the particle size of the positive electrode active material is limited to be small and the specific surface area is large, which is beneficial to reduce the interface transfer impedance and significantly improve the power performance of the secondary battery. By controlling the volume particle size distribution Dv10 and Dv99 of the positive electrode active material to limit the particle size distribution, the particle size of the positive electrode active material is small and the particle size distribution is concentrated, which is beneficial to further improve the cycle performance and power of the secondary battery. At the same time, by doping the lithium iron phosphate, by controlling the type of doping elements including Al and / or at least one transition metal element other than Fe, and controlling the mass proportion of M in the M-doped lithium iron phosphate to be 200ppm-1500ppm, the lithium iron phosphate material is structurally modified to improve its lattice stability, effectively improve the cycle performance, and also have a certain improvement effect on its power performance.

[0079] Among them, the mass proportion of M in M-doped lithium iron phosphate is too much, resulting in excessive distortion and deterioration of power performance. Therefore, controlling the mass proportion of M in M-doped lithium iron phosphate is 200ppm-1500ppm, which is beneficial to improving the power performance and cycle performance of the secondary battery. Exemplarily, the doping mass of M in M-doped lithium iron phosphate is 200ppm, 300ppm, 400ppm, 500ppm, 600ppm, 700ppm, 800ppm, 900ppm, 1000ppm, 1100ppm, 1200ppm, 1300ppm, 1400ppm, 1500ppm, or any value between any two values. In summary, the positive electrode plate provided in the present application, by simultaneously regulating the particle size of the positive active material, the type of doping element and the doping amount within the above range, cooperates with each other through the mutual action of various parameters, so that when the positive electrode plate is applied to the battery, the battery takes into account both high power performance and high cycle performance.

[0080] Illustratively, the volume particle size distribution Dv50 of the positive electrode active material is 0.3μm, 0.4μm, 0.5μm, 0.6μm, 0.7μm, 0.8μm, 0.9μm, 1.0μm, 1.1μm, 1.2μm, 1.3μm, 1.4μm, 1.5μm, 1.6μm, 1.7μm, 1.8μm, 1.9μm, 2.0μm, 2.1μm, 2.2μm, 2.3μm, 2.4μm, 2.5μm, 2.6μm, 2.7μm, 2.8μm, 2.9μm, 3μm, any one of or between any two values.

[0081] Illustratively, the volume particle size distribution particle size Dv10 of the positive electrode active material is any value of 100nm, 150nm, 200nm, 250nm, 300nm, 350nm, 400nm, 450nm, 500nm, 550nm, 600nm, 65nm, 700nm, 750nm, 800nm ​​or between any two values.

[0082] In some embodiments, the mass proportion of M in the M-doped lithium iron phosphate is 300 ppm-1500 ppm.

[0083] Controlling the mass proportion of M in M-doped lithium iron phosphate within the above range is beneficial to optimizing the power performance and cycle performance of the battery.

[0084] Exemplarily, the mass proportion of M in M-doped lithium iron phosphate is 300ppm, 400ppm, 450ppm, 500ppm, 550ppm, 600ppm, 650ppm, 700ppm, 750ppm, 800ppm, 850ppm, 900ppm, 950ppm, 1000ppm, 1100ppm, 1200ppm, 1300ppm, 1400ppm, 1500ppm, any value or between any two values.

[0085] In some embodiments, the transition metal element includes at least one of Mn, V, Ti, Zr, Ni, Co, and Nb.

[0086] By doping lithium iron phosphate with the above-mentioned doping elements, it is beneficial to improve the stability of the material structure and enhance the power performance and cycle performance of the battery.

[0087] Illustratively, M is one or more of Ti, Nb, and Al.

[0088] Optionally, M is Ti and / or Nb.

[0089] It should be noted that the M-doped lithium iron phosphate is bulk doped, and the bulk doping may be uniform doping or non-uniform doping.

[0090] In some embodiments, the mass proportion of M in the interior of the M-doped lithium iron phosphate is less than the mass proportion of M on the surface of the M-doped lithium iron phosphate. The above-mentioned "interior" and "surface" are relative concepts, and the "interior" can be the center of the M-doped lithium iron phosphate particle, but is not limited to the center of the M-doped lithium iron phosphate particle. The mass proportion of M in the interior of the M-doped lithium iron phosphate is less than the mass proportion of M on the surface of the M-doped lithium iron phosphate, and it is not limited to the linear increase from the interior to the surface of the M-doped lithium iron phosphate particle. It can also be nonlinearly increasing, as long as the content of the M element on the surface is greater than that in the interior, and it is not strictly controlled to gradually increase along the above direction.

[0091] Taking advantage of the fact that the mass proportion of M in the interior of the M-doped lithium iron phosphate is smaller than the mass proportion of M on the surface of the M-doped lithium iron phosphate, that is, the M element is enriched on the surface of the M-doped lithium iron phosphate particles, is beneficial to improving the interface stability and the cycle stability of the battery.

[0092] Among them, in order to achieve that the mass proportion of M inside the M-doped lithium iron phosphate is less than the mass proportion of M on the surface of the M-doped lithium iron phosphate, the preparation method of the M-doped lithium iron phosphate particles includes but is not limited to a solid phase sintering method, which includes: dispersing a certain proportion of iron source (iron phosphate), lithium source (lithium carbonate), carbon source (polyvinyl alcohol) & doped metal M source in a solvent (pure water or methanol / ethanol mixed solution) and mixing and dispersing, after coarse grinding, fine grinding, batching, and then passing ~220°C hot air through spray drying, calcining at ~750°C in an inert atmosphere for ~9h, and crushing, sieving to remove magnetism and other processes to obtain M-doped lithium iron phosphate material. Since the ability of atoms to diffuse from the outside to the inside is limited during solid phase sintering, an M-doped lithium iron phosphate material with a surface rich in transition metal M can be obtained.

[0093] In some embodiments, the positive electrode active material layer further includes a shell layer coated on the surface of the M-doped lithium iron phosphate. wherein the shell comprises carbon; and / or; The shell layer accounts for 1%-5% of the mass of the positive electrode active material; and / or; The thickness of the shell is 1nm-10nm.

[0094] Among them, the carbon content in the coating layer is beneficial to improving the conductivity of the positive electrode active material and avoiding direct contact between lithium iron phosphate and the electrolyte, which is beneficial to improving the structural stability of the core.

[0095] If the shell ratio is too low to the mass of the positive electrode active material, it will affect electron transmission, and if it is too high, it will affect the compaction density. Therefore, controlling it within the above range is beneficial to improving the energy density and cycle performance of the battery.

[0096] Illustratively, the shell layer accounts for any value of 1.0%, 1.5%, 2.0%, 2.5%, 3.0%, 3.5%, 4.0%, 4.5%, 5.0% of the mass of the positive electrode active material, or is between any two values.

[0097] If the shell layer is too thick, the kinetic decay of the positive electrode active material will lead to a decrease in capacity. Therefore, controlling the thickness of the coating layer within the above range is beneficial to improving the cycle performance and power of the battery.

[0098] Exemplarily, the thickness of the shell layer is any value of 1 nm, 2 nm, 3 nm, 4 nm, 5 nm, 6 nm, 7 nm, 8 nm, 9 nm, 10 nm, or between any two values.

[0099] In some embodiments, the positive electrode active material layer includes a conductive agent, and the conductive agent may include at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.

[0100] In some embodiments, the conductive agent in the positive electrode active material layer includes at least carbon nanotubes.

[0101] The selection of carbon nanotubes can effectively reduce the expansion of the electrode during the cycle, thereby improving the power performance and cycle performance of the secondary battery.

[0102] In some embodiments, the carbon nanotubes are single-walled carbon nanotubes, and the specific surface area of ​​the carbon nanotubes is 400 m 2 / g-1600m 2 / g, tube diameter is 1.2nm-4.8nm, and tube length is >50nm.

[0103] It can be understood that the above-mentioned specific surface area, tube diameter and tube length are all the average specific surface area, average tube diameter and average tube length of single-walled carbon nanotubes.

[0104] Among them, the test method of the tube length of the carbon nanotubes includes: using the argon ion polishing CP method to make the electrode into a test sample, and using a scanning electron microscope (SEM) to capture and obtain an image of the carbon nanotubes in the base coating in the CP cross-sectional view of the test sample. For example, 50 carbon nanotubes are randomly selected in the image, and the average length of the carbon nanotubes is measured as the tube length through image analysis.

[0105] The test method of the diameter of the carbon nanotube includes: taking the disassembled positive electrode sheet, using a focused ion beam to find the corresponding CNTs, cutting them respectively, observing and measuring the diameters under a TEM, and calculating the average value as the diameter of the carbon nanotube.

[0106] Specific surface area test: The test method refers to the standard GB / T19587-2004 "Gas adsorption BET determination of solid surface area". It can be understood that the average specific surface area of ​​single-walled carbon nanotubes is obtained in the test here. The single-walled carbon nanotubes in the above range are selected. Because of their high strength and good flexibility, when the pole piece expands, the single-walled carbon nanotubes can better restrain the expansion of the active particles themselves and the expansion between the active particles. And because of their better conductivity, controlling its parameters within the above range can effectively reduce the expansion of the pole piece during the cycle, thereby improving the power performance and cycle performance.

[0107] For example, the specific surface area of ​​the carbon nanotubes is 400 m 2 / g、600m 2 / g、800m 2 / g、1000m 2 / g、1200m 2 / g、1400m 2 / g、1600m 2 The tube diameter is any value among 1.2nm, 1.6nm, 1.8nm, 2.0nm, 2.2nm, 2.4nm, 2.6nm, 2.8nm, 3.0nm, 3.2nm, 3.4nm, 3.6nm, 3.8nm, 4.0nm, 4.2nm, 4.4nm, 4.6nm, 4.8nm or any value between any two values.

[0108] Exemplarily, the tube length is less than or equal to 15μm, that is, the tube length is greater than 50nm and less than or equal to 15μm. Exemplarily, the tube length is any value among 55nm, 100nm, 500nm, 1μm, 2μm, 3μm, 4μm, 5μm, 6μm, 7μm, 8μm, 9μm, 10μm, 11μm, 12μm, 13μm, 14μm, 15μm or between any two values.

[0109] In some embodiments, the conductive agent of the positive electrode active material layer further includes carbon black.

[0110] That is, the conductive agent of the positive electrode active material layer includes carbon nanotubes and carbon black. Through morphology compounding, the conductive effect is better. At the same time, carbon black can enhance electrolyte infiltration and ion conductivity, which is beneficial to improving battery power performance and cycle performance.

[0111] In some embodiments, the positive active material layer includes a binder.

[0112] As an example, the binder may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorine-containing acrylate resin.

[0113] In some embodiments, the positive electrode active material layer includes a binder; Wherein, the weight average molecular weight of the binder satisfies 40W-150W; and / or, The binder includes at least one of polyvinylidene fluoride, polytetrafluoroethylene, polyacrylic acid, polyvinyl alcohol, polyacrylonitrile and polyolefin.

[0114] Test of weight-average molecular weight of polymer materials: Waters 2695 Isocratic HPLC gel chromatograph (differential refractive index detector 2141) was used. A polystyrene solution sample with a mass fraction of 3.0% was used as a reference, and a matching chromatographic column (oily: Styragel HT5 DMF 7.8*300mm + Styragel HT4) was selected. A 3.0% adhesive glue solution was prepared with purified N-methylpyrrolidone (NMP) solvent, and the prepared solution was allowed to stand for one day for use. During the test, tetrahydrofuran was first drawn with a syringe, rinsed, and repeated several times. Then 5 ml of the experimental solution was drawn, the air in the syringe was removed, and the needle tip was wiped dry. Finally, the sample solution was slowly injected into the injection port. After the indication stabilized, the data was obtained and the weight-average molecular weight was read.

[0115] If the weight average molecular weight of the binder polymer material is too small, the bonding strength will be poor, and if it is too large, the slurry will easily agglomerate. Therefore, the weight average molecular weight of the binder polymer material is controlled to meet 40W-150W, which can ensure the bonding strength of the electrode without deteriorating the processing performance.

[0116] Exemplarily, the weight average molecular weight of the binder polymer material satisfies any value of 40W, 60W, 80W, 100W, 120W, 140W, and 150W or is between any two values.

[0117] In some embodiments, the positive electrode active material layer includes, by mass percentage, 95%-99% positive electrode active material, 0.2%-1% conductive agent, 0.5%-3% binder, and 0-1% surfactant.

[0118] The surfactant includes at least one of an anionic surfactant and a nonionic surfactant. The surfactant can disperse the small particles of positive electrode active materials, improve the performance of the slurry, and prevent the small particles from agglomerating. As an example, the ionic surfactant is at least one of sulfate and alkylphenyl sulfonate, wherein the sulfate is at least one of sodium sulfate and potassium sulfate, the alkylphenyl sulfonate is at least one of sodium dodecyl sulfate, sodium dodecylbenzene sulfonate, and potassium perfluorooctane sulfonate, and the nonionic surfactant includes but is not limited to at least one of octylphenol polyoxyethylene ether and polyvinyl pyrrolidone.

[0119] Under the premise of controlling the particle size selection and particle size distribution of the positive electrode active material, the mass proportion of each component in the positive electrode active material layer is further controlled, so as to optimize the internal pore structure of the electrode sheet and improve the power performance and cycle performance of the secondary battery under the premise of controlling the addition amount of the positive electrode active material to a high level.

[0120] Furthermore, the mass percentage of the binder in the positive electrode active material layer is 0.5%-2%, and the mass percentage of the surfactant in the positive electrode active material layer is 0.1%-1%. The secondary battery has both high power performance and cycle performance.

[0121] In some embodiments, the positive electrode sheet further includes a positive electrode current collector and a primer layer, wherein the primer layer is disposed between the positive electrode current collector and the positive electrode active material layer.

[0122] The undercoat layer is actually a conductive adhesive layer, which contains a binder, a conductive agent and a dispersant. The undercoat layer is arranged between the positive electrode collector and the positive electrode active material layer to improve the bonding force between the positive electrode collector and the positive electrode active material layer.

[0123] For example, the coating amount of the primer layer on the current collector is 5 mg / 1540.25 mm 2 -10mg / 1540.25mm 2 . Hereinafter, the embodiments of the present application will be described. The embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If no specific techniques or conditions are indicated in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. If the manufacturer is not indicated in the reagents or instruments used, they are all conventional products that can be obtained commercially.

[0124] Example 1

Preparation of positive electrode

[0125] The positive electrode active material includes Ti-doped lithium iron phosphate with a doping amount of 800 ppm, and a carbon layer coated on the surface of the Ti-doped lithium iron phosphate, and the carbon layer accounts for 3% of the mass of the positive electrode active material.

[0126]

Preparation of negative electrode sheet

[0127]

Preparation of electrolyte

[0128]

Isolation film

[0129]

Battery preparation

[0130] Examples 2-7 and Comparative Examples 1-4 The difference between each embodiment and comparative example lies in the positive electrode active material layer, and the parameters different from those of embodiment 1 are shown in Table 1 below.

[0131] The difference between Comparative Example 1 and Example 1 is only that the content of the doping element is different.

[0132] The difference between Comparative Example 2 and Example 1 is that the particle size and specific surface area of ​​the positive electrode active material are different.

[0133] The only difference between Comparative Example 3 and Example 1 is that no doping is performed.

[0134] Table 1 Differences between Examples 1-12 and Comparative Examples 1-3

[0135] Note: The doping element content in Table 1 refers to the content of the doping element in M-doped lithium iron phosphate. In addition, the batteries prepared in the above embodiments and comparative examples were subjected to the following performance tests.

[0136] 【20% SOC DC impedance test (25℃)】 In a constant temperature environment of 25°C, the battery of the device was left to stand for 10 minutes, and then discharged at a constant current of 0.33C to the lower voltage limit of the battery. After standing for 10 minutes, it was charged at a constant current of 0.33C to an upper voltage limit of 3.8V, and then charged at a constant voltage to a current of 0.05C. After standing for 10 minutes, it was discharged at a constant current of 0.33C to a lower voltage limit of 2.0V and the discharge capacity C0 was recorded at this time. Then it was left to stand for 10 minutes, and then charged at a constant current of 0.33C to 0.2C0. After standing for 10 minutes, it was discharged at 4C0 for 30s and the DC impedance value and discharge power of the battery were calculated (DC impedance = (voltage before discharge - voltage after discharge) / discharge current. The smaller the impedance value, the stronger the discharge capacity.

[0137] [45℃ Cycle 1500 SOH Test Method & 1500 Cycle Expansion Force Test Method] Take a fresh battery cell, bring a three-piece steel fixture, install a Copre pressure sensor to monitor the expansion force, and the preload force is 3000N; The cycle process is as follows: in a constant temperature environment of 45°C, the prepared battery is charged at a constant current of 0.5C to the upper limit voltage, and then charged at a constant voltage at the upper limit voltage to a current ≤0.05C, allowed to stand for 5 minutes, and then discharged at a constant current of 1C to the lower limit voltage. This is a cyclic charge and discharge process; repeat the above steps until the battery cell cycle reaches 1500 cycles, and read the SOH retention rate of the battery cell when the cycle reaches 1500 cycles and the battery cell expansion force at this time.

[0138] The results are shown in Table 2.

[0139] Table 2 Test results

[0140] According to Tables 1 and 2, the present application simultaneously regulates the particle size of the positive electrode active material, the type of doping element and the doping amount to cooperate with each other so that the secondary battery has high power performance and better cycle performance.

[0141] Among them, according to the comparison of Examples 1-5 and Comparative Examples 1 and 2, it can be seen that although the doping elements can improve the power, the mass proportion of the doping elements in the M-doped lithium iron phosphate is too large, resulting in excessive distortion and deterioration of the power performance. The mass proportion of the doping elements in the M-doped lithium iron phosphate is controlled to be 200ppm-1500ppm, which is conducive to improving the power performance and cycle performance of the secondary battery. Further, when the mass proportion of the doping elements in the M-doped lithium iron phosphate is 300ppm-1500ppm, it is conducive to further improving the power performance and cycle performance of the secondary battery.

[0142] According to Examples 1, 6-8, it can be seen that different doping elements will affect the power performance of the secondary battery. When the doping elements are Ti and Nb, the secondary battery has better power performance and cycle performance.

[0143] It can be seen from Examples 1, 9-10 and Comparative Example 3 that the particle size distribution of the positive electrode active material affects the power performance and cycle performance of the secondary battery. Among them, Comparative Example 3 has too large a particle size, resulting in too large a 20% SOC DC impedance, which deteriorates the power performance.

[0144] According to Examples 1, 11, and 12, the conductive agent composed of a compound of carbon black sp and carbon nanotubes is more conducive to improving the power performance and cycle performance of the secondary battery than the conductive agent consisting only of carbon nanotubes or carbon black sp, and carbon nanotubes can effectively improve the power performance and cycle performance of the secondary battery compared to carbon black sp.

[0145] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and exerting the same effect within the scope of the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the main purpose of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.

Claims

1. A battery cell, characterized in that: Comprising a positive electrode plate, the positive electrode plate comprising a positive electrode active material layer, the positive electrode active material layer comprising a positive electrode active material, the positive electrode active material having a volume particle size distribution Dv50 of 0.3 μm-3 μm, a volume particle size distribution Dv10 of 100 nm-800 nm, and a volume particle size distribution Dv99<20 μm; The positive electrode active material includes M-doped lithium iron phosphate, wherein M includes Al and / or at least one transition metal element except Fe, and the mass proportion of M in the M-doped lithium iron phosphate is 200 ppm-1500 ppm.

2. The battery cell according to claim 1, characterized in that: The mass proportion of the M in the M-doped lithium iron phosphate is 300ppm-1500ppm.

3. The battery cell according to claim 1, characterized in that: The transition metal element includes at least one of Mn, V, Ti, Zr, Ni, Co, and Nb.

4. The battery cell according to claim 1, characterized in that: The specific surface area of ​​the positive electrode active material is 10 m 2 / g-20 m 2 / g.

5. The battery cell according to claim 1, characterized in that: The mass proportion of M in the interior of the M-doped lithium iron phosphate is smaller than the mass proportion of M on the surface of the M-doped lithium iron phosphate.

6. The battery cell according to claim 1, characterized in that: The positive electrode active material layer further includes a shell layer coated on the surface of the M-doped lithium iron phosphate. wherein the shell layer comprises carbon; and / or; The shell layer accounts for 1%-5% of the mass of the positive electrode active material; and / or; The thickness of the shell layer is 1 nm-10 nm.

7. The battery cell according to any one of claims 1 to 6, characterized in that: The positive electrode active material layer includes a conductive agent, and the conductive agent includes carbon nanotubes.

8. The battery cell according to claim 7, characterized in that: The carbon nanotubes are single-walled carbon nanotubes, and the specific surface area of ​​the carbon nanotubes is 400 m 2 / g -1600m 2 / g, tube diameter is 1.2 nm-4.8 nm, and tube length is >50 nm.

9. The battery cell according to claim 7, characterized in that: The conductive agent also includes carbon black.

10. The battery cell according to any one of claims 1 to 6, characterized in that: The positive electrode active material layer includes a binder; Wherein, the weight average molecular weight of the binder satisfies 40W-150W; and / or, The binder includes at least one of polyvinylidene fluoride, polytetrafluoroethylene, polyacrylic acid, polyvinyl alcohol, polyacrylonitrile and polyolefin.

11. The battery cell according to any one of claims 1 to 6, characterized in that: In terms of mass percentage, the positive electrode active material layer includes: 95%-99% of the positive electrode active material, 0.2%-1% of a conductive agent, 0.5%-3% of a binder, and 0-1% of a surfactant.

12. The battery cell according to any one of claims 1 to 6, characterized in that: The positive electrode plate further includes a positive electrode current collector and an undercoat layer, wherein the undercoat layer is disposed between the positive electrode current collector and the positive electrode active material layer.

13. A secondary battery, characterized in that: A battery cell comprising the battery cell according to any one of claims 1 to 12.

14. An electrical device, characterized in that: Includes the secondary battery as claimed in claim 13.

Citation Information

Patent Citations

  • Secondary battery and electric equipment

    CN115472898A

  • Carbon-coated lithium iron phosphate positive active material, preparation method thereof, positive pole piece containing carbon-coated lithium iron phosphate positive active material and lithium ion battery

    CN116601798A

  • Positive electrode material, positive electrode plate and battery

    CN117117196A

  • Preparation method of LiFePO4 / C composite material doped with metal ions

    CN118529714A

Cited By

  • Positive plate and lithium ion secondary battery

    CN120072849A

  • Battery cell, battery device, electric device, and energy storage device

    CN120300267A

  • Battery cell, battery device, power consuming device, and energy storage device

    CN120300267B

  • Battery cell, battery device, electric device, and energy storage device

    CN120300268A

  • Battery cells, battery packs, electrical devices, and energy storage devices

    CN120300268B